2006
DOI: 10.1111/j.1439-0507.2006.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of new and conventional antimycotics against fluconazole‐susceptible and non‐susceptible Brazilian Candida spp. isolates

Abstract: The substantial increase in the rate of azole resistant Candida spp. yeast infections has become a serious treatment problem requiring new and more active antifungal agents. In this study, the in vitro activities of ravuconazole and albaconazole were compared with those of amphotericin B, flucytosine, itraconazole and fluconazole against 162 Brazilian isolates of Candida spp. from which 48 isolates had previously shown lower susceptibility or resistance to fluconazole. Ravuconazole susceptibility ranged from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Examples of recent approaches to antifungal treatments include new triazoles such as ravuconazole and albaconazole, which display a broad-spectrum activity against yeast and filamentous fungi, including species resistant to fluconazole and itraconazole [22]. In addition, the use of inhibitors from other steps of sterol biosynthesis is an alternative approach to the development of new chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of recent approaches to antifungal treatments include new triazoles such as ravuconazole and albaconazole, which display a broad-spectrum activity against yeast and filamentous fungi, including species resistant to fluconazole and itraconazole [22]. In addition, the use of inhibitors from other steps of sterol biosynthesis is an alternative approach to the development of new chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Alves et al 27 found that among isolates susceptible to fluconazole, the activity of flucytosine was highest against C. albicans (84.6%) and C. glabrata (94.1%). Additionally, they reported that 40% of C. krusei isolates were susceptible to flucytosine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they reported that 40% of C. krusei isolates were susceptible to flucytosine. Alves et al 27 have argued that the great potential of flucytosine against C. glabrata has not been sufficiently explored and that this antifungal may be used as a treatment option when resistance to azoles is observed. In our study, the C. glabrata isolate was susceptible to fluconazole and flucytosine.…”
Section: Discussionmentioning
confidence: 99%
“…The substance with the highest in vitro activity is compound 20, which was supported by results investigations, reported between 2000 and 2008. A recent name of compound 20 is Albaconazol (UR-9825) [53][54][55][56] and it is undergoing Phase II clinical trials, but its future is uncertain. Further investigation is needed in order to gain insight into the precise relationships linking chemical structure and pharmacological activity for fungicide substances in vivo.…”
Section: Discussionmentioning
confidence: 99%